Скляні кубки з поховань могильника Лісові Гринівці в Південному Побужжі - Демидко, С.Ю.; Строцень, Б.С.; Щепаченко, В.І. (Археологія, 2024)
Статтю присвячено публікації скляних посудин із поховань 7, 13 і 18 черняхівського могильника Лісові Гринівці 3а, дослідженого під час проведення рятівних робіт на будівництві автодороги Хмельницький-Шепетівка у 2010—2011 роках. In the article, the publication of glass vessels from the burials of the Cherniakhiv burial ground Lisovi Hrynivtsi 3a is presented. The site was discovered by Serhii Demydko in 2010 during the construction of the Khmelnytskyi-Shepetivka road. Rescue excavations of the preserved part of the burial site in 2010–2011 revealed 21 burials, three of which (burials nos. 7, 13 and 18) contained glass beakers among the accompanying funeral material. Two of the vessels can be attributed to the Eggers type 230, which widely circulated in different regions of the European Barbaricum mainly in the second and third quarters of the 4th century. Another one belongs to the Sântana de Mureș type. Similar artefacts are also recognised in the Roman provinces as beakers of the AR 69, Trier 54, or 47f types according to L. Barkoczi. The finds of such vessels outside the Limes are concentrated exclusively within the Cherniakhiv culture area and are mainly associated with the final stage of its existence, i.e. the last quarter of the 4th — first third of the 5th centuries. The glass vessels come from inhumations oriented to the west. In the grave pit, the goblets were placed mainly next to the skull of the buried person. The combination of chronological markers suggests that the set of items from the burial no. 13 can be dated to the third quarter of the 4th century, and the assemblages from burials nos. 7 and 18 to the last quarter of the 4th to the first third of the 5th centuries. Certain differences in the geographical distribution of glass vessels found in Lisovi Hrynivtsi, in our opinion, may indicate different origins of these glassware types. Based on this assumption, we can suggest the existence of at least two vectors of supply of glass vessels to the local community of the Cherniakhiv culture, one of which is probably not associated with the Roman Empire.